POROUS STRUCTURE OF ROAD CONCRETE - M. K. Pshembaev; V. V. Girinsky; Ya. N. Kovalev; V. N. Yaglov; S. S. Budnichenko (Наука и техника)
Having a great number of concrete structure classifications it is recommended to specify the following three principal types: microstructure – cement stone structure; mesostructure – structure of cement-sand mortar in concrete; macrostucture – two-component system that consists of mortar and coarse aggregate. Every mentioned-above structure has its own specific features which are related to the conditions of their formation. Thus, microstructure of cement stone can be characterized by such structural components as crystal intergrowth, tobermorite gel, incompletely hydrated cement grains and porous space. The most important technological factors that influence on formation of cement stone microstructure are chemical and mineralogical cement composition, its grinding fineness, water-cement ratio and curing condition. Specific cement stone microstructure is formed due to interrelation of these factors. Cement stone is a capillary-porous body that consists of various solid phases represented predominantly by sub-microcrystals of colloidal dispersion. The sub-microcrystals are able adsorptively, osmotically and structurally to withhold (to bind) some amount of moisture. Protection of road concrete as a capillary-porous body is considered as one of the topical issues. The problem is solved with the help of primary and secondary protection methods. Methods of primary protection are used at the stage of designing, preparation and placing of concrete. Methods of secondary protection are applied at the operational stage of road concrete pavement. The paper considers structures of concrete solid phase and characteristics of its porous space. Causes of pore initiation, their shapes, dimensions and arrangement in the concrete are presented in the paper. The highest hazard for road concrete lies in penetration of aggressive liquid in it and moisture transfer in the cured concrete. Water permeability of concrete characterizes its filtration factor which depends on curing time and conditions and operational conditions as well.